2020
DOI: 10.1016/j.ajoc.2020.101002
|View full text |Cite
|
Sign up to set email alerts
|

Axial length shortening in a myopic child with anisometropic amblyopia after wearing violet light-transmitting eyeglasses for 2 years

Abstract: Purpose To report a case in which the axial length (AL) shortened and the choroid thickened due to the use of violet light-transmitting eyeglasses. Observations A 4-year-old boy with high myopia was referred to Keio University Hospital. He was prescribed standard eyeglasses. Six months after the first visit, his best-corrected visual acuities were 1.2 and 0.4 in the right and left eyes, respectively, with the standard eyeglasses, and he was diagnosed with anisometropic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Short-term decreases in AL have been reported following orthokeratology treatment, 24 , 25 and persistent AL shortening was reported in a 4-year-old child given violet light-transmitting eyeglasses, which led to −0.20 AL over 2 years. 26 In the ATOM1 study, AL shortened −0.14 mm in subjects using 1% atropine eye drops, but the proportion and range were not reported. 9 In this study, clinically significant AL shortening was observed in fewer than 10% of subjects using 0.01% atropine but this was even more common in the RLRL group (20.6%), consistent with three previous studies reporting that RLRL decreased AL over 6 months in a large proportion of children.…”
Section: Discussionmentioning
confidence: 96%
“…Short-term decreases in AL have been reported following orthokeratology treatment, 24 , 25 and persistent AL shortening was reported in a 4-year-old child given violet light-transmitting eyeglasses, which led to −0.20 AL over 2 years. 26 In the ATOM1 study, AL shortened −0.14 mm in subjects using 1% atropine eye drops, but the proportion and range were not reported. 9 In this study, clinically significant AL shortening was observed in fewer than 10% of subjects using 0.01% atropine but this was even more common in the RLRL group (20.6%), consistent with three previous studies reporting that RLRL decreased AL over 6 months in a large proportion of children.…”
Section: Discussionmentioning
confidence: 96%
“…The spectral modulation of light reaching the retina can also offer promising therapeutics for myopia. A recent study by Ofuji et al 261 have shown that wearing VL-transmitting glasses for 2 years, and engaging in outdoor activity for 2 h can reduce ocular axial length and increase choroidal thickness in a child with high myopia. As reported by Torii et al , 148 an increased expression of EGR1 gene may have led to this protective effect of VL- transmitting glasses against myopia.…”
Section: The Development Of Light-therapy Strategies For Myopiamentioning
confidence: 99%
“…Environmental factors, particularly light, have emerged as important contributors to the progression of myopia [7][8][9] . Our previous research highlighted the preventive effects of violet light (VL; 360-400 nm wavelength) on myopia progression, not only in experimental animals of myopia [10][11][12] but also in humans [13][14][15][16] . Furthermore, we found that VL exposure was effective in suppressing myopia progression in a transmission-dependent manner (from 40-100%) in a murine model of lens-induced myopia 12 .…”
Section: Introductionmentioning
confidence: 99%